PRODUCTIVITY AND PROCESS ANALYSIS REINFORCED CONCRETE BEAM WORK ON JIIPE GRESIK MOSQUE-BKMS CONSTRUCTION PROJECT - RANGGA ADI SAPUTRA; Intan Maya Sari; Donny July Prasetya (DEARSIP : Journal of Architecture and Civil, 2025)
Controlling labor productivity in construction projects has a very important role. For example, labor productivity in the early stages of a project can have a major impact on the accuracy of schedules or plans that have been prepared. This study aims to find out the process of implementing block work in the Mosque Construction Project-BKMS JIIPE Gresik and compare the productivity of labor in the installation of beam reinforcement with productivity standards as stated in the Minister of PUPR Regulation No. 1 of 2022. Observations were carried out directly in the field by recording the number of workers, the volume of work, and the duration of time (working hours) on the B1 Block work for eight working days, starting at 07.00–11.00 WIB. The break time lasted at 11.00–13.00 WIB, and the work continued until 16.00 WIB. In addition, recording is also carried out at the end of working hours every day to obtain process data and worker productivity values. The reinforced concrete block work in this project uses conventional methods which include the stages of preparation, measurement, ironing, formwork installation, checking, casting, dismantling of formwork, and treatment (curing) which are all carried out at the project site with the support of certain tools. The results of the observation showed that the average labor productivity (blacksmith) for the installation of B1 beam reinforcement work reached 147,390 kg/OH, while the highest productivity was 210,532 kg/OH and the lowest was 93,986 kg/OH. The results of calculations based on the Minister of PUPR Regulation No. 1 of 2022 show that the standard productivity for blacksmith labor is 142,857 kg/OH. Based on the results of the analysis, it was found that the average productivity of workers in the field had a value of 1,031 times greater than the standard of the Ministerial Regulation on PUPR.